RUWATAN DALAM TEKS TUTUR KUMARATATWA ANALISIS SEMIOTIKA - Sri Andayani, Ni Luh Putu (Humanis; Volume 11. No2. Mei 2015, 2015)
Tutur is one of the types of literature that contains the value of philosophy, religion, and the value of life, in every speech story certainly contains in it the values of life which later can be a reflection of the wider community. Research on the text genre is still a little tutr done, because the script said because it becomes interesting material to serve as the object of research, one of which is the Tutur Kumaratatwa. Research on the text of the Tutur Kumaratatwa studied the structure and semiotics. Structural analysis aims to examine the structure of the script while the semiotic analysis aims to analyze the signs which contain a meaning in the Tutur Kumaratatwa and indirectly this study may provide information to the public about the contents of the Tutur Kumaratatwa. At the stage of data collection, the method used is the method of reading the text being studied as a research object and translate it, also used literature study methods and methods of interviews with sources who are considered capable in traditional literature, especially in the form of tutur. The third method is assisted by the technique of recording and recording to avoid errors because the data were forgotten. Structure analysis Tutur Kumaratatwa composed of structural analysis which consists of the language in the text of the Tutur Kumaratatwa, incidents, plot (plot), character, setting, theme, and the mandate. While the semiotic analysis Tutur Kumaratatwa discusses ruwatan that is in the text of the Tutur Kumaratatwa.
Keywords: speech, structure, semiotics